DARI TAFSIR ANTROPOSENTRIS KE TAFSIR EKOSENTRIS: REKONSTRUKSI FILSAFAT PENDIDIKAN ISLAM DALAM PERSPEKTIF KRISIS LINGKUNGAN GLOBAL - Robiah Adawiyah (Jurnal Reflektif, 2026)
The global environmental crisis indicates that ecological problems are not merely technical but paradigmatic, rooted in how humans conceptualize their relationship with nature. This article aims to analyze the interconnection between Qur’anic interpretation, Islamic theology, and philosophy of education in shaping an Islamic ecological paradigm, and to formulate a model of Islamic educational philosophy oriented toward sustainability. The study employs a library research approach using thematic exegetical analysis and a philosophy of education framework. The findings reveal that the dominance of anthropocentric interpretations in modern intellectual traditions has contributed to the theological legitimation of environmental exploitation. However, contemporary Islamic thought demonstrates a significant shift toward cosmological interpretations emphasizing divine unity, cosmic balance, and human responsibility as an ecological trust. Based on this foundation, the article proposes a model of ecological Islamic educational philosophy grounded in a relational ontology of God–human–nature, an integrative epistemology of revelation and science, and an axiology of sustainability. This model positions Islamic education as a transformative process that cultivates both ecological and spiritual consciousness, thereby offering a potential epistemological contribution of Islam to the global discourse on sustainable education.